Modeling acoustic transitions in speech by state-interpolation hidden Markov models - Deng, Li; Kenny, Patrick; Lennig, Matthew; Mermelstein, Paul (IEEE Transactions on Signal Processing, 1992)
We present a new type of HMM for vowel-to-consonant (VC) and consonant-to-vowel (CV) transitions based on the locus theory of speech perception. The parameters of the model can he trained automatically using the Baum-Welch algorithm and the training procedure does not require that in- stances of all possible CV and VC pairs be present. When incorporated into an isolated word recognizer with a 75 000 word vocabulary we find that it leads to a modest improvement in recognition rates.